KEBOLEHAN PEMIMPIN PEREMPUAN DALAM POLITIK DI INDONESIA PERSPEKTIF ISLAM - Ines Prasheila Kusmastuti; Al Muazzami Al Muazzami (Kalam: Jurnal Agama dan Sosial Humaniora, 2023)
This research further examines women's leadership in politics in Indonesia from an Islamic perspective by examining Surah An-Nur verse 55 and Hadith Nasai Number 5293. This type of research is library research with qualitative data analysis and presented descriptively. This research uses a ta'lily approach and a normative approach. The results of this research state that Surah An Nur verse 55 legitimizes that to be a leader you must do pious deeds. This pious deed is not only limited to men, so women who do pious deeds are certainly worthy of being leaders. On the other hand, Nasai hadith Number 5293 only applies specifically to Persia at that time. As times change, women now have a lot of access to education, leadership, and so on. Women's leadership in Indonesia can be seen from the many great women who become leaders. From a juridical perspective, the law also facilitates women's leadership in the political realm by giving women the right to representation. Therefore, women's leadership in politics in Indonesia from an Islamic perspective is permissible.